Patients with psychiatric diagnoses have increased odds of morbidity and mortality in elective orthopedic surgery. (February 2021) - Brown, Avery; Alas, Haddy; Bortz, Cole; Pierce, Katherine E.; Vasquez-Montes, Dennis; Ihejirika, Rivka C; Segreto, Frank A.; Haskel, Jonathan; Kaplan, Daniel James; Segar, Anand H.; Diebo, Bassel G.; Hockley, Aaron; et al.
Highlights: Psychiatric diagnoses have an impact on the treatment and outcomes of patients undergoing elective orthopedic procedures. Afflicted patients are more likely to have higher costs surgeries, extended length of stays, and death during their admission. Abstract: Psychiatric diagnoses (PD) present a significant burden on elective surgery patients and may have potentially dramatic impacts on outcomes. As ailments of the spine can be particularly debilitating, the effect of PD on outcomes was compared between elective spine surgery patients and other common elective orthopedic surgery procedures. This study included 412, 777 elective orthopedic patients who were concurrently diagnosed with PD within the years 2005 to 2016. 30.2% of PD patients experienced a post-operative complication, compared to 25.1% for non-PD patients (p < 0.001). Mood Disorders (bipolar or depressive disorders) were the most commonly diagnosed PD for all elective Orthopedic procedures, followed by anxiety, then dementia (p < 0.001). Logistic regression analysis found PD to be a significant predictor of higher cost to charge ratio (CCR), length of stay (LOS), and death (all p < 0.001). Between, hand, elbow, and shoulder specialties, spine patients had the highest odds of increased CCR and unfavorable discharge, and the second highest odds of death (all p < 0.001).